LEIOMYOMA: ITS VARIANTS AND SECONDARY CHANGES A FIVE-YEAR STUDY - Naz, Shabana; Rehman, Abdur; Riyaz, Anila; Jehangir, Fouzia; Naeem, Shagufta; Iqbal, Touqeer (Journal of Ayub Medical College Abbottabad, 2019)
Background: Abnormal uterine bleeding is a common problem encountered by the gynaecologists, leiomyoma being one of the most common causes. An accurate knowledge of the different variants and secondary changes occurring in leiomyoma is essential as some of these may mimic malignancy clinically, radiologically and histologically. Some important examples being atypical, cellular and mitotically active leiomyoma. Similarly, hydropic and myxoid change can be misdiagnosed as malignancy. While dealing with these variants and changes, leiomyosarcoma although a rare tumour has to be excluded because of the difference in management. Hence a comprehensive knowledge of all the variants is mandatory to avoid misdiagnosis. Methods: This study was carried out at the Pathology Department of Ayub Medical College Abbottabad where 964 cases of leiomyoma of the female genital tract were studied. These cases were received during the period January 2013 to December 2017. Result: The most common variant of leiomyoma was cellular leiomyoma while hyaline degeneration was the most common secondary change identified. Conclusion: Accurate knowledge of these variants and degenerative changes in leiomyomas are mandatory to prevent misdiagnosis and over treatment along with undue stress to the patient. Secondly it is important to identify variants which require follow-up. Keywords: Hysterectomy, Leiomyoma variants, Secondary changes, Hyaline degeneration